Examples of remote sensing application in agriculture monitoring - Mananze, Sosdito (2023)
Mananze, Sosdito. 2023. Examples of remote sensing application in agriculture monitoring. PowerPoint presentation given during the Project Inception Workshop, VIP Grand Hotel, Maputo, Mozambique, April 20, 2023